Revisiting the dyonic Majumdar-Papapetrou black holes - Mazharimousavi, Seyedhabibollah; Halilsoy, Mustafa (Tubitak Scientific & Technological Research Council Turkey, 2016)
We extend the Majumdar-Papapetrou solution of the Einstein-Maxwell equations, which are implied generally for static electric charge in nonrotating metrics, to encompass equally well magnetic charges. In the absence of Higgs and non-Abelian gauge fields, 'dyonic' is to be understood in this simpler sense. Cosmologically this may have far-reaching consequences, to the extent that existence of multimagnetic monopole black holes may become a reality in our universe. Infalling charged particle geodesics may reveal, through particular integrals, their inner secrets, which are screened from our observation.
Keywords: Black-holes; Majumdar-Papapetrou; Exact solutions